KNOWLEDGE, ATTITUDE, AND PERCEPTION OF INDIAN POPULATION ABOUT GENERIC VERSUS BRANDED MEDICINES: A WEB-BASED STUDY - RATHI, HEENA; BIYANI, MOHIT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the current study is to evaluate knowledge, attitude, and perception of Indian Population about generic versus Branded Medicines. Methods: It was a cross-sectional prospective web-based questionnaire study. We used an application name Google form and link (https://forms.gle/ RJA6XvPeJy6TXNzN9) was created. Total 537 participants took part in our study. Nineteen questions related to knowledge, attitude, and perception about generic versus branded medicines were asked in the questionnaire. Results: In our study, 78.6% participants had heard about generic medicines. About 66.2% agreed that they understand the difference between both the medicines. About 74.5% knew that there is price difference in both the medicines. According to only 22.1% of our study participants’ doctors preferred generic medicines and 37.7% thought that chemists preferred to sell generic medicines than branded ones. About 40.4% knew that generic medicines are promoted by Indian government but surprisingly, 63.3% said that they are unaware of any government rules regarding this. About 44.9% did not know about the type of drugs on their prescription. About 54.8% preferred to buy generic medicines but interesting fact is that 74.3% had not asked their doctors to prescribe generic medicines but 41.7% believed that generic medicines should be promoted. Conclusion: Results of our study revealed that poor knowledge, negative attitude, and false perception regarding generic medicines are the main hindrance of sits acceptance by general population.